Recurrent neck swelling after iodinated contrast media administration - Cunha, Inês Machado (2021)
A 74-year-old male with an abdominal aortic aneurism reported 2 episodes of neck swelling 16 hours after an abdominal CT with iodinated contrast media that reappeared in a subsequent CT, although the use of pre-medication. The tests used to exclude the hypersensitivity hypothesis where negative and once a new CT where needed we decided to do it with close monitoring. We performed a facial picture and cervical ultrasound exam before and 24 hours after the exam. The neck swelling and the ultrasound findings 24 hours after the CT made the diagnosis of contrast induced sialoadenitis possible. Contrast induced sialadentis is an uncommon adverse reaction to iodinated contrast media. As it presents with neck swelling it is important to exclude a hypersensitivity reaction because it's further limitations and make a differential diagnosis.